Special topics in policing: critical issues and global perspectives, volume 1 - Albrecht, James F.; Heyer, Garth den (Springer, 2024)
This book comprehensively examines five key areas of concern across the field of policing. These critical issues include: police use of force, police ethics and integrity, traffic safety, police-community collaboration, and optimizing organizational performance and service delivery. The chapters that follow provide a global, multi-faceted approach to analyze these core professional issues, examine them through sociological and theoretical lenses, and ultimately propose policy recommendations to ensure optimal professionalism and organizational effectiveness. The book focuses on issues, including: • Enhancing public trust and confidence • Effective crime control • Rule of law • Social justice • Best procedures and practices This book is ideal for upper-level undergraduate and graduate-level students, criminal justice and law enforcement practitioners and policy makers, and criminal justice and criminology researchers.